Factors of tendency on students' interest towards Arabic language: a study at Management and Science University / Mohd Fahimi Zakaria and Mohd Adi Amzar Muhammad Nawawi - Zakaria, Mohd Fahimi; Muhammad Nawawi, Mohd Adi Amzar (Universiti Teknologi MARA, 2020)
The offering of Arabic in Management and Science (MSU) is not new, even since its inception. It is in line with government policy through the Ministry of Education Malaysia to promote Arabic as an international professional field. To date, there have been no specific studies related to the journey of Arabic teaching and learning at MSU as there are no such requirements today. Therefore, this study was conducted by those with a background in Arabic seeking to determine what factors are likely to be of interest to MSU students in Arabic during the current semester of September 2019. Researcher adopt a library study through a qualitative approach that leads to text analysis through application of methods descriptive surveys, a set of online surveys using google sheets and distributed to 30 students who took Arabic from a variety of programs and faculties. This study shows that the dominant factor is the desire to learn a new language among students compared to other factors such as refining their knowledge, working in the Arab world, understanding the Quran, responding to challenges and fun teaching aids. This study also records some of the important factors that influence this factor: gender, semester of study, program, faculty, age and subject. This proves that students' interest in the subject matter of the Arabic is not only due to certain factors, but also by other influences which also play an important role in the formation of the student's own interest.